Development Of Learning Media for Physical Education and Health Subjects in Grade VIII of SMP Negeri 24 OKU - Yamanto Isa; Johan Eka Wijaya DN; Fitri Bugis (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
This study aims to develop and evaluate the feasibility of Adobe Flash CS6-based learning media for Physical Education, Sports, and Health (PJOK) subjects for Grade VIII students at SMP Negeri 24 OKU. The study employed a research and development (R&D) approach, conducted through stages of design, development, expert validation, and field testing. The data were obtained from media experts, learning design experts, material experts, and students as research subjects. The population of this study consisted of all Grade VIII students, with samples selected through staged trials: individual testing (3 students), small-group testing (7 students), and field testing (28 students). Data were collected using validation sheets and questionnaires and analyzed using descriptive statistical techniques, including percentage feasibility analysis. The results indicate that the developed learning media achieved very good feasibility criteria based on expert validation and student trials. Media, design, and materials experts rated the product as highly feasible, while student responses showed positive perceptions of ease of use, attractiveness, and clarity of learning content. These findings demonstrate that Adobe Flash CS6-based learning media is suitable for use as a learning support tool in PJOK subjects at the junior high school level and has the potential to enhance student engagement and learning motivation.